A new space-vector-modulation algorithm for a three-level four-leg NPC inverter - Rojas, Felix; Kennel, Ralph; Cardenas, Roberto; Clare, Jon C.; Diaz, Matias (Institute of Electrical and Electronics Engineers (IEEE), 2016)
For power conversion systems interfaced to 4-wire supplies, four-leg converters have become a standard solution. A four-leg converter allows good compensation of zero-sequence harmonics and full utilization of the dc-link voltage. These are very important features when unbalanced and/or non-linear loads are connected to the system. This paper proposes a 3D-SVM algorithm and provides a comprehensive analysis of the algorithm implemented on a three-level, four-leg NPC converter. The algorithm allows a simple definition of the different switching patterns and enables balancing of the dc-link capacitor voltages using the redundancies of the converter states. A resonant controller is selected as the control strategy to validate the proposed SVM algorithm in a 6kW experimental rig.